Multicultural Politics: Rasism, Ethnicity and Muslims in Britain - Tariq Modood (University of Minnesota Press, 2005)
Muslims have come to be perceived as the 'Other' that is most threatening to British society. This book argues that what begins as a narrative of racial exclusion and black-white division has been complicated by cultural racism, Islamophobia and an unexpected challenge to secular modernity. Moreover, the idea of 'race' as underclass has had to contend with the creation of middle class formations and high levels of participation in higher education among some non-white groups. These plural divisions are not intractable but require us to rethink simplistic and monistic ideas about racism, secularism, liberalism and what it means to be British. Tariq Modood has developed a unique and influential perspective out of his sense that the concerns of South Asians lie at the heart of 'race relations' in Britain. This book gathers together a number of his key sociological, political and theoretical interventions, together with a substantial new Introduction and Conclusion, allowing readers to engage with a distinctive analysis of race and religion. Key Features: * Combines a discussion of racism and Muslim politics in Britain * Offers an interdisciplinary combination of empirical sociology with political theory of multiculturalism * Challenges the secularist bias of liberals and social scientists